Reverse Shock Emission from Misaligned Structured Jets in Gamma-Ray Bursts - Sen-Lin Pang; Zi-Gao Dai (The Astrophysical Journal)
The afterglow of gamma-ray bursts (GRBs) has been extensively discussed in the context of shocks generated during an interaction of relativistic outflows with their ambient medium. This process leads to the formation of both a forward and a reverse shock. While the emission from the forward shock, observed off-axis, has been well-studied as a potential electromagnetic counterpart to a gravitational-wave-detected merger, the contribution of the reverse shock is commonly overlooked. In this paper, we investigate the contribution of the reverse shock to the GRB afterglows observed off-axis. In our analysis, we consider jets with different angular profiles, including two-component jets, power-law structured jets, Gaussian jets, and “mixed jets” featuring a Poynting-flux-dominated core surrounded by a baryonic wing. We apply our model to GRB 170817A/GW170817 and employ the Markov Chain Monte Carlo method to obtain model parameters. Our findings suggest that the reverse shock emission can significantly contribute to the early afterglow. In addition, our calculations indicate that the light curves observable in future off-axis GRBs may exhibit either double peaks or a single peak with a prominent feature, depending on the jet structure, viewing angle, and microphysics shock parameters.